'Student tutors go online' - Investigation of cognitive and social congruence in online student tutorials - a longitudinal study. Issue 1 (31st December 2022) - Loda, Teresa; Berner, Nils; Erschens, Rebecca; Nikendei, Christoph; Zipfel, Stephan; Herrmann-Werner, Anne
ABSTRACT: The concept of peer-assisted learning (PAL) has been implemented at many medical faculties. Due to the Covid-19 pandemic, parts of the medical education experience transitioned to digital formats. However, little is known about PAL and online student tutorials. PAL is effective due to cognitive and social congruence. This study aims to investigate these concepts in an online student tutorial on taking a patient's medical history. This longitudinal study took place in a preclinical communication course on how to take a patient's medical history. In an online student tutorial, the students learned how to take a patient's psychosocial medical history. Using standardised questionnaires, cognitive and social congruence were assessed. T-tests of independent samples were performed for data comparison. The participants included 128 second-year medical students and 5 student tutors. Cognitive congruence (Mstudent = 4.19 ± 0.56; Mstudenttutor = 4.04 ± 0.57) and social congruence (MStudent = 4.25 ± 0.56; MStudenttutor = 4.06 ± 0.57) were high for both students and student tutors in the online setting. In comparison to the face-to-face group, students in the online setting considered the student tutors to be significantly (p < .05) more socially congruent. Learning success increased during the course; however, it was not influenced by cognitive congruence. Cognitive and social congruence are high in an online setting. The students' learning success increased during the online tutorial. Based on the higher level of social congruence, student tutors might be very motivated to be open and approachable in an online setting. Simultaneously, students might pay more attention and participate actively in the online setting. Social and cognitive congruence contribute to the effectiveness of online student tutorials and, thus, online student tutorials should be integrated into medical training.